Don Giovanni [videorecording (DVD)] - Da Ponte, Lorenzo, 1749-1838; Strehler, Giorgio, 1921-1997; Battistoni, Carlo; Gruberova, Editá, 1946-2021; Murray, Ann, 1949-; Mentzer, Susanne; Araiza, Francisco; Allen, Thomas, 1944-; Desderi, Claudio; De Carolis, Natale; Kopčák, Sergej; Muti, Riccardo; et al. (La Scala collection., 2004)
Outstanding RAI television archive recording of the opera performance of Da Ponte's tale of lust and subversion from the Teatro alla Scala.